World's Largest SWRO Plant Sets Benchmark for Low‐Cost Desalinated Water. Issue 5 (1st May 2014) - Unknown
Abstract : Finished Water is a photo feature that profiles working operators and utilities in the news, particularly new and renovated facilities.